Beyond the First Cry: Prevalence and Risk Factors of Postpartum Depression in Sindh, Pakistan - Meghji, Kumayl Abbas; Memon, Areesha Mushtaque; Ramzan, Ayesha Muhammad; Memon, Isra; Rehman, Sidra; Sultan, Faiza (Journal of Postgraduate Medical Institute, 2025)
Objective: To assess PPD prevalence across hospitals in Sindh, Pakistan, and determine its association with various maternal, neonatal, and socioeconomic risk factors. Methodology: This multicenter cross-sectional study was conducted between April and September 2023 at various hospitals in Hyderabad and Karachi. A total of 219 mothers aged 20-40 years with recent singleton births were included in the study. The Edinburgh Postnatal Depression Scale (EPDS) and a structured questionnaire were used to gather data. Statistical analysis was done using SPSS (version 22) with chi-square tests and Pearson's correlation analysis. Results: The mean EPDS score among participants was 18.18±5.90, with 66.21% screening positive for PPD. Significant positive correlations were found between PPD and maternal age (r=0.96, p<0.001), BMI (r=0.95, p<0.001), and significant negative correlation with maternal education level (r=-0.93, p<0.001). Factors such as low income, rural residence, extended family structure, cesarean delivery, non-exclusive breastfeeding, multiparity, lack of spousal support, neonatal complications, and previous miscarriages were significantly associated with PPD (p<0.05). Conclusion: PPD is highly prevalent in Sindh and is significantly associated with a multitude of maternal, neonatal, and socioeconomic risk factors such as maternal age, education, income, and multiparity, among others.